PENGARUH NILAI UTILITARIAN,NILAI HEDONIS, PENGALAMAN PELANGGAN, KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN SONNY VAIO - Erik Wardhana (Jurnal Ekonomi dan Industri, 2019)
The background of this research was examined the influences of trust and affect on increasing likelihood to purchase luxury brands. The objectives of this research was analyzed the effect of utilitarian value on brand loyalty, the effect to hedonic value on brand loyalty, the effect of customer experience on brand loyalty, the effect of brand trust on brand loyalty. A sampling with purposive sampling techniques of fourty four customer of Sony Vaio as the respondents provided the data that were analyzed for this study. Using a sub-set of the sample consisting of fourty four customer of Sony Vaio was used to test four hypothesized relationships in the model. The result of this research conclude that the effect of positively and significantly utilitarian value, hedonic value, customer experience, brand trust toward brand loyalty on Sony vaio consumer.